Environmental wellbeing in the context of sustainable development: Evidence from post-communist economies - Ulman, Simona-Roxana; Mihai, Costica; Cautisanu, Cristina; Brumă, Ioan-Sebastian; Coca, Oana; Stefan, Gavril (Frontiers in Environmental Science, 2022)
Considering diverse national contexts, there are differences in the capacity of countries in terms of their ability to attain sustainability in its three main dimensions. The present study puts the economic, social, and environmental indicators face-to-face from 19 post-communist economies across the 2006–2020 period. It emphasizes the main vulnerabilities at the level of the analyzed countries, concentrates on these weak points, and offers concrete explanations regarding the main social and economic factors, exerting a negative influence on them. Consequently, placing climate and energy, with their major components, i.e., energy use, energy savings, greenhouse gases, and renewable energy, at the center of the analysis, as the major weak points of environmental wellbeing within the analyzed group of countries, the nature of the influence of human and economic wellbeing upon each of them is evidenced using panel data-specific methods (pooled, fixed, and random effects). The general results obtained showed the following: 1) the components of environmental wellbeing registered a different evolution among post-communist economies; 2) climate and energy components were the main vulnerabilities in terms of environmental sustainability; 3) these environmental components were closely linked to both components of economic and social dimensions; and 4) the determinants of energy use, energy savings, greenhouse gases, and renewable energy were different in the selected group of countries. This study draws attention to the fact that the patterns of development applied in the group of post-communist economies seem to strengthen sustainable goals, especially with regard to economic and human wellbeing. Moreover, while directing its focus on the main urgent environmental vulnerabilities and encouraging their strengthening by not putting the economic dimension in the center of interest, it supports the theoretical perspective of sustainable wellbeing, based on sustainability and ecological economics.